2019
DOI: 10.1007/s10853-019-03642-1
|View full text |Cite
|
Sign up to set email alerts
|

Microneedle array sensors based on carbon nanoparticle composites: interfacial chemistry and electroanalytical properties

Abstract: Conductive microneedle patches consisting of carbon nanoparticles embedded in a polystyrene matrix have been prepared using micro-moulding techniques. The interfacial properties of the structures before and after electrochemical etching have been characterised using X-ray photoelectron spectroscopy and contact angle. Anodisation of the needles leads to a significant increase in oxygen functionality and is shown to dramatically improve the electroanalytical capabilities of the microneedle array. The detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…When polyaniline is deposited, as shown in Figure 7(b), the lamella structure on the surface of the ITO conductive glass can be clearly seen, and the thickness of the polyaniline layer structure is relatively uniform. [44][45][46] In Figure 7(c), it can be clearly observed that the electrode surface is loaded with a layer of palladium. The palladium particles are small, and the combination of PANI presents a fibrous network structure, which is evenly distributed, and has a significant spatial expansion effect, and the specific surface area is increased.…”
Section: Hydroxyl Radical Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…When polyaniline is deposited, as shown in Figure 7(b), the lamella structure on the surface of the ITO conductive glass can be clearly seen, and the thickness of the polyaniline layer structure is relatively uniform. [44][45][46] In Figure 7(c), it can be clearly observed that the electrode surface is loaded with a layer of palladium. The palladium particles are small, and the combination of PANI presents a fibrous network structure, which is evenly distributed, and has a significant spatial expansion effect, and the specific surface area is increased.…”
Section: Hydroxyl Radical Detectionmentioning
confidence: 99%
“…Figure7shows the SEM image of the unloaded ITO conductive glass, PANI/ITO supporting electrode, and Pd/PANI/ITO under the same magnification.It can be seen from Figure7(a) that the surface of the unloaded ITO conductive glass is clean and smooth. When polyaniline is deposited, as shown in Figure7(b), the lamella structure on the surface of the ITO conductive glass can be clearly seen, and the thickness of the polyaniline layer structure is relatively uniform [44][45][46]. …”
mentioning
confidence: 99%
“…In most cases, moulds based on PDMS tend to be the replication workhorses and offer an easy route through which to manipulate the material composition of the MN and thereby refine its properties [7][8][9][10][11], This micromoulding approach has obvious advantages for drug delivery applications -providing a simple means through which to incorporate the therapeutic agent, but it has also been shown to enable the production of MN arrays for sensing applications. The potential viability of the approach was initially demonstrated using composite palladium / polycarbonate and nanocarbon/ polystyrene MN structures [12,13]. Moreover, the rich interfacial chemistry of the carbon surface can enable the immobilization of enzymes (ie.via carbodiimide coupling with the surface carboxyl functionalities) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensor technology is a growing area of research in the field of biomedical instrumentation. The integration of nanomaterials with micro/nano-fluidic based wearable sensors find their use in military applications [27,28], sports [29] and healthcare [30,31]. Apart from detection of various biochemicals or biomarkers, these smart dressings can also sense changes in physical parameters such as temperature, moisture, blood pH, etc.…”
Section: Introductionmentioning
confidence: 99%